Finite element analysis of rectangular composite plates subjected to a uniformly distributed load - Chin, Yan Hunk (Nanyang Technological University, 2024)
This project is meant to study the maximum bending deflections of composite laminates when subjected to uniform loading and in various configurations, namely with varying laminate thicknesses, stacking sequences and boundary conditions. Anti-Symmetric Cross Ply and Symmetric Cross Ply laminates with 2-ply to 16-ply thicknesses are modelled using the Finite Element Analysis software ANSYS to study the effect of bending-extension coupling on laminate bending deflections. Bending-extension coupling terms B11 are present in Anti-Symmetric Cross Ply laminates but not in Symmetric Cross Ply laminates. Previous studies indicate that coupling effect increases the bending deflection of a laminate. This study reveals that only the 2-ply Anti-Symmetric laminate shows a higher bending deflection due to coupling effect, with the other ply thicknesses of the Anti-Symmetric laminate having a lower bending deflection than the Symmetric laminate. The effects of the various simply supported boundary conditions S1 to S4 are analysed and it shows that S1 conditions largely correspond with S3 conditions, whereas S2 conditions largely correspond with S4 conditions, even when the boundary conditions are mixed. Overall, the results from Finite Element Analysis are validated by theoretical calculations using previously derived formulas and the MATLAB software to a high degree of accuracy. Therefore, the findings from ANSYS can be deemed to be reliable. This study reveals certain phenomenon that can be used to gain a deeper understanding of composite materials, such as the convergence of maximum bending deflection after the ply thickness exceeds 6-ply.